2021
DOI: 10.1186/s12879-021-06535-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimating case fatality risk of severe Yellow Fever cases: systematic literature review and meta-analysis

Abstract: Background Case fatality risk (CFR), commonly referred to as a case fatality ratio or rate, represents the probability of a disease case being fatal. It is often estimated for various diseases through analysis of surveillance data, case reports, or record examinations. Reported CFR values for Yellow Fever vary, offering wide ranges. Estimates have not been found through systematic literature review, which has been used to estimate CFR of other diseases. This study aims to estimate the case fata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…The estimated CFR of YFV in humans identified in this review is consistent with that recently reported in a global review with a CFR of 36% for Africa [77]. Such a high CFR could be due to delays or deterrents in seeking care during the early less sever phase of the disease or delayed clinical diagnosis of cases [62,76].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 86%
See 1 more Smart Citation
“…The estimated CFR of YFV in humans identified in this review is consistent with that recently reported in a global review with a CFR of 36% for Africa [77]. Such a high CFR could be due to delays or deterrents in seeking care during the early less sever phase of the disease or delayed clinical diagnosis of cases [62,76].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 86%
“…Such a high CFR could be due to delays or deterrents in seeking care during the early less sever phase of the disease or delayed clinical diagnosis of cases [62,76]. It should also be noted that African population is more at risk of contracting the yellow fever virus and of developing severe forms and death due to a low rate of vaccination coverage and daily activities that bring them closer to vectors such as agriculture, livestock, hunting, and deforestation [77][78][79][80]. Also, the existence in Africa of other health conditions such as malnutrition, tuberculosis, malaria and, HIV are other factors that could be associated with this high of YFV CFR [81][82][83].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Infected persons present with a broad spectrum of clinical disease, ranging from asymptomatic infections and mild febrile illness to severe disease and death. It is estimated that 15-25% of infected symptomatic persons progress to severe disease with a case fatality rate of 20-60% [6,14].…”
Section: Introductionmentioning
confidence: 99%
“…Viruses 2022, 14, 1204 2 of 10 been a concern for public authorities owing to the low vaccination coverage in non-endemic and endemic areas [1][2][3][4]. Epidemiologically, fatality in severe cases of YF is estimated to be approximately 31-45%, indicating the public health importance of this disease [5].…”
Section: Introductionmentioning
confidence: 99%
“…The virus is then released into the bloodstream and is transported to multiple organs such as the kidney, heart, spleen, lung, and liver. The liver is the most affected organ in humans [5][6][7].…”
Section: Introductionmentioning
confidence: 99%